Changes in midlife fitness, body mass index, and smoking influence cancer incidence and mortality: A prospective cohort study in men - Robsahm, Trude E. (Cancer Med, 2019)
Cancer prevention efforts include modification of unhealthy lifestyle, such as smoking cessation and resisting gain in body weight. Although physical activity is inversely related to risk of several cancers, it is poorly studied whether changes in physical activity or fitness influence future cancer risk. Thus, we aimed to investigate whether changes in midlife cardiorespiratory fitness (CRF), body mass index (BMI), and smoking habits influence cancer incidence and mortality. The study cohort includes 1689 initially healthy men, aged 40‐59 years. Measurements of CRF, BMI and information on smoking habits were collected in two repeated waves, 7 years apart. Cox regression models estimated associations as hazard rates (HR) with 95% confidence intervals (CI), between midlife changes in the modifiable lifestyle factors and cancer incidence and mortality. The men were followed prospectively for more than 30 years. Compared to CRF loss (>5%), improved CRF (>5%) was associated with lower cancer incidence (HR 0.81, 95% CI 0.67‐0.98) and mortality (HR 0.70, 95% CI 0.54‐0.92), and maintaining the CRF stable yielded lower cancer incidence (HR 0.76, 95% CI 0.61‐0.95). No association was seen for BMI gain, but maintaining the BMI stable was related to lower cancer incidence (HR 0.77, 95% CI 0.60‐0.98), compared to BMI loss. Continue smoking was associated with higher cancer incidence and mortality, compared to men who stopped smoking. In particular, this study adds new knowledge about the potential preventive role of CRF in cancer development and emphasizes lifestyle modification as a highly important effort in cancer prevention.